PROVISION OF SPECIAL SERVICES FOR ELDERLY VOTERS AT POLLING STATIONS DURING THE 2024 REGIONAL ELECTIONS - AZHARI, FARIZ ANTONIUS; Titiek Kartika Hendrastiti; Adityo Pratikno Ramadhan (PT. Media Akademik Publisher, 2025)
Abstract. This research analyzes the provision of special services for elderly voters at polling stations during the 2024 Regional Head Election in Bengkulu City using Søren Winter's Integrated Implementation Model. Through qualitative methods including in-depth interviews, observations, and documentation studies, significant gaps were identified between KPU Decree Number 66 of 2024 and field implementation. The top-down policy formulation without regional KPU involvement resulted in formalistic adaptation lacking local context. Limited understanding among KPPS officers, minimal resource allocation, and absence of a specialized elderly services unit in the Bengkulu City KPU contributed to inconsistent service quality across polling stations. KPPS officers developed discretion and adaptation strategies based on personal values, while elderly voters demonstrated passive responses due to limited awareness of their rights. Though elderly voter participation rates remained high at approximately 70-75%, participation quality was compromised by accessibility barriers. Effective implementation requires a participatory approach to policy formulation, adequate resource allocation, enhanced officer capacity, cross-sectoral collaboration, and structured evaluation mechanisms to safeguard elderly citizens' political rights and promote inclusive democracy.